PELAKSANAAN PEMBELAJARAN SENI BUDAYA (MUSIK) MENGGUNAKAN MEDIA AUDIOVISUAL DI KELAS VIII-2 SMP NEGERI 30 PADANG - Rahmat Fadil; Yos Sudarman; Esy Maestro (SENDRATASIK UNP, 2018)
Abstract This article aimed to explain about the implementation of culture and arts learning (music) using audiovisual media in class VIII-2 of SMP Negeri 30 Padang. The background of the research was the interest of researcher to use audiovisual media in classroom learning in line with the order and composition of the material subject given. The type of research was qualitative research with a descriptive approach. The object of the study was the teacher and students who were studying culture and arts (music) in the subject matter of regional song appreciation, namely in class VIII-2 of SMP Negeri 30 Padang. The instruments of this research were observation and interview. The results showed that when audiovisual media used in music learning by paying attention to the order and suitability of the subject matter, then the use of audiovisual media would be able to attract students' attention in fostering understanding in learning. It was because the audiovisual learning media was not limited to power point and video display; sometimes the media was displayed separately from the subject matter delivered by the teacher in the classroom. Keywords:           Audiovisual Media, Culture and Arts Learning, Regional Music